Decrease in Respiratory Related Hospitalizations in Tracheostomy-Dependent Children Who Tolerate Passy-Muir Valve Use. (June 2021) - Li, Lilun; Wikner, Emily; Behzadpour, Hengameh; Perez, Geovanny; Mudd, Pamela
Objective: To assess the effect of Passy-Muir ® Valve (PMV) tolerance on respiratory illness and respiratory related hospital admissions in tracheostomy-dependent children. Methods: Retrospective cohort study of 262 patients who underwent tracheostomy placement between 2012 and 2018 at a tertiary free-standing children's hospital. Outcome measures studied were number of reported upper respiratory infections and respiratory related hospitalizations per year (RRH/year). Results: About 135 (51.5%) tracheostomy-dependent children underwent PMV trials, and 106 (78.5%) of these children were able to tolerate PMV for at least 1 hour daily. When comparing children who tolerated PMV versus those who did not, the latter group had significantly higher rates of subglottic stenosis but no significant differences in RRH/year or average age. In those children who tolerated PMV and achieved routine use of PMV > 1 hour/day, an average of 1.14 RRH/year occurred prior to PMV tolerance, as compared with 0.57 RRH/year after PMV tolerance ( P  = .003). Multivariate analysis shows that in patients <2 years, there is a significant decrease in RRH/year after PMV tolerance is attained (1.53 vs 0.76, P  = .001), independent of indication for tracheostomy. Conclusion: In tracheostomy-dependent children who tolerate PMV use routinely >1 hour/day there are decreased rates of respiratory related hospitalizations (RRH). Children <2 years of age have the most impact of RRH, with rates that are significantly lower with routine use of the PMV.